Glasgow in the Year of Revolutions: A Commentary and Analysis of the Glasgow Riots of 1848 (Groundings Undergraduate, 2024)
In 1848, a series of revolutions and demonstrations occurred across Europe, though Britain was comparatively unaffected aside from generally peaceful Chartist agitation and a handful of small riots. One of these riots occurred in Glasgow between 6th-8th March, following increasing unrest surrounding the scale of poverty and unemployment, involving thousands of Glaswegians and inspiring further unrest in towns across Scotland. Using a variety of sources, though principally local and national newspapers, this paper will assess the context preceding the riot, provide a microhistory of the riot itself, its consequences, and explore the significance of the riots within the history of Glasgow, and within the context of Scottish and British Radicalism. It will argue that the riots demonstrate both the scale and circumstances of poverty within Glasgow in the 1840s, and the social divisions existing within Glasgow’s Chartist movement.
Keywords: Chartism; Glasgow; Riots; 1848; Revolution; Local History